2000
DOI: 10.1182/blood.v95.7.2240.007k08_2240_2245
|View full text |Cite
|
Sign up to set email alerts
|

Increased transplant-related morbidity and mortality in CMV-seropositive patients despite highly effective prevention of CMV disease after allogeneic T-cell–depleted stem cell transplantation

Abstract: We evaluated the efficacy, toxicity, and outcome of preemptive ganciclovir (GCV) therapy in 80 cytomegalovirus (CMV)-seropositive patients allografted between 1991 and 1996 and compared their outcome to 35 seronegative patients allografted during the same period. Both cohorts were comparable with respect to diagnosis and distribution of high- versus standard-risk patients. All patients received a stem cell graft from an HLA-identical sibling donor, and grafts were partially depleted of T cells in 109 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In most immunocompetent hosts, CMV is asymptomatic, and MHC class-I restricted CD8 T cell responses keep CMV viraemia and disease in check (3,4). In the immunocompromised, however, CMV reactivation can have serious adverse effects, as seen in transplant patients under immunosuppressive regimens (5), in the context of AIDS (6,7) and in the elderly (8,9). During the 1980's, human immunodeficiency virus (HIV) pandemic, CMV co-infection was a leading cause of morbidity and mortality in HIV-infected individuals (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In most immunocompetent hosts, CMV is asymptomatic, and MHC class-I restricted CD8 T cell responses keep CMV viraemia and disease in check (3,4). In the immunocompromised, however, CMV reactivation can have serious adverse effects, as seen in transplant patients under immunosuppressive regimens (5), in the context of AIDS (6,7) and in the elderly (8,9). During the 1980's, human immunodeficiency virus (HIV) pandemic, CMV co-infection was a leading cause of morbidity and mortality in HIV-infected individuals (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common viral infections throughout the world, the adverse effects of CMV infection in transplantation have been long noted. 17,29 However, the exact impact of pretransplant recipients’ CMV serostatus on liver graft injury has not been clearly addressed, although a prevailing majority of the transplant recipients are CMV seropositive (R+). Here through the clinical analysis, rat orthotopic liver transplantation model, and in vitro studies, we found that CMV latency in the recipients aggravated small-for-size graft injury after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested an emerging role of CMV latency in chronic graft diseases. 15-18 The exact effect of CMV latency in small-for-size liver graft injury, however, has not been examined because of the complexity of confounding factors in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…The survival and non-relapse mortality is worst for CMV seronegative donor/seropositive recipient (D−/R+), followed by CMV seropositive donor/seropositive recipient (D+/R+) [6]. The other risk factors that increase the risk of CMV infection after HSCT include in vivo or ex vivo T cell depletion, high dose steroids, HLA mismatched or unrelated donors, and GVHD [7][8][9][10][11]. The use of high doses of antithymocyte globulin (ATG) for in vivo T cell depletion may be associated with lower survival [12].…”
Section: Risk Factors For CMV Disease After Allo-hsctmentioning
confidence: 99%
“…Studies have shown that CMV replication increases the risk of GVHD [4]. Studies have also shown a significant association between CMV positive serology and development of GVHD, with increased transplant-related mortality and decreased overall survival [2,10].…”
Section: Bidirectional Relationship Between CMV and Gvhdmentioning
confidence: 99%